MODELAGEM E SIMULAÇÃO DA PRODUÇÃO DE PEQUI NO TERRITÓRIO KALUNGA DE GOIÁS UTILIZANDO A METODOLOGIA SYSTEM DYNAMICS - BUZIN, Estevão Julio Walburga Keglevich de (2009)
This work presents the social and environmental factors related to community Kalunga of Goiás and its area of occupation that justifies the care to determine the possibilities for use of Territory Kalunga. Considering the importance of various interactions existing means of production factors that affect the biological, sociological and marketing, it was developed a modelling system and simulation of production pequi of the Kalunga territory in Goiás using the methodology of system dynamics. The developed system was performed with 200 replicates, assuming a period of 20 years of installation of the enterprise. To perform the analysis of sustainability of the project it was applied of a group of indicators that consider the environmental, social, economic and political. The results indicate that the implementation of a project for the production of pequi is a profitable and sustainable project in all aspects considered.